Relationship between Multiplier, Employee Job Attitude, and Employee Engagement - Yondonrenchin, Munkhdemberel; Zanabazar, Altanchimeg (Archives of Business Research, 2023)
Nowadays, with the rapid development of the business sector and increasing competition, the significance of effective leadership in managing business organizations has escalated significantly. In this fiercely competitive environment, it is imperative for leaders to recognize and respond to the emotions of their employees. Consequently, they need to place great emphasis on employee attitudes, satisfaction, loyalty, and engagement. This study aims to examine the correlation between the multipliers which is a new style of modern leadership, employee job attitudes, and employee engagement. The research encompassed a survey administered to employees of a well-established trade and services company with over two decades of operational experience. Quantitative data were processed using software tools such as SPSS 23.0 and Smart PLS 4.0, which are extensively employed in social science research. A total of 85 employees participated in the study, and for verification and testing the proposed hypothesis in the study, we conducted various statistical analyses inclusive of factor analysis, reliability analysis, correlation analysis, and structural equation models (SEMs). According to the results of the analysis, it was shown that a significant and positive influence of multiplier on both employee job attitude and employee engagement. Furthermore, employee job positive attitude leads to an increase in employee engagement. Additionally, the study’s results indicate a noteworthy finding: it was observed that employee job attitude plays a mediating role in the relationship between the multiplier and employee engagement.